2020
DOI: 10.1002/cac2.12076
|View full text |Cite
|
Sign up to set email alerts
|

miR‐495 and miR‐5688 are down‐regulated in non‐small cell lung cancer under hypoxia to maintain interleukin‐11 expression

Abstract: Background Hypoxia is a hallmark of cancer and is associated with poor prognosis. However, the molecular mechanism by which hypoxia promotes tumor progression remains unclear. MicroRNAs dysregulation has been shown to play a critical role in the tumor and tumor microenvironment. Here, we investigated the roles of miR‐495 and miR‐5688 in human non‐small cell lung cancer (NSCLC) and their underlying mechanism. Methods The expression levels of miR‐495 and miR‐5688 in human NSCLC tissue specimens were measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Data were presented as mean ± SD. *P < 0.05, **P < 0.001 Dysregulation of miRNAs have been reported to contribute to tumorigenesis and progression in various can-cers [15,17,18,61]. The miR-205 and miR-200 family members are known to suppress cell EMT and tumor metastasis by inhibiting ZEB1 and SIP expression in cancer cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Data were presented as mean ± SD. *P < 0.05, **P < 0.001 Dysregulation of miRNAs have been reported to contribute to tumorigenesis and progression in various can-cers [15,17,18,61]. The miR-205 and miR-200 family members are known to suppress cell EMT and tumor metastasis by inhibiting ZEB1 and SIP expression in cancer cells [16].…”
Section: Discussionmentioning
confidence: 99%
“… 46 Moreover, IL-11 was found to exert oncogene effects in various cancers, such as colorectal cancer, 47 liver cancer, 48 and non-small cell lung cancer. 49 Recently, various studies indicated that IL-11 was upregulated in breast cancer tissues compared with normal tissues, and high expression of IL-11 was associated with poor prognosis in breast cancer patients. 50 , 51 Further study revealed that IL-11 plays a significant role in breast cancer progression, especially the well-documented capacity to promote breast cancer bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have shed light on the role of miRNAs in cancer. For example, hypoxic conditions enhance lung cancer progression by decreasing the expression of miRNA-495 and miRNA-5688 and subsequently increasing IL-11 levels [ 298 ]. Moreover, decreased expression of miRNA-100 and miRNA-125b paves the way for overexpression of IGF2 and subsequent cancer stem cell features in hepatocellular carcinoma [ 299 ].…”
Section: Exosomal Mirnasmentioning
confidence: 99%